Prospective efficacy of molecular preoperative diagnostics of papillary thyroid carcinoma - MANKOVSKAYA, Svetlana V.; DEMIDCHIK, Yuri E.; YAMASHITA, Shunichi (Acta medica Lituanica, 2010)
Background. The diagnostic efficacy of the molecular analysis that included determination of papillary thyroid carcinoma (PTC) marker gene expression levels and BRAF mutation in fine-needle aspiration biopsy material was evaluated in a prospective study of patients with thyroid nodules.Materials and methods. Totally, 36 patients (29 females and 7 males) with thyroid nodules were included in the study. The mRNA expression of genes (SFTPB and TFF3) was estimated in relation to a housekeeping gene level (KPNA4) by means of duplex RT-PCR followed by the band intensity measurement. Detection of BRAF mutation was performed by PCR followed by direct sequencing.Results. In 25/32 (78.1%) cases, results of the molecular test were in agreement with the cytological diagnosis (7/7 PTC and 18/25 non-PTC) further confirmed by histological examination of tissues surgically removed from all seven PTC patients and 10 individuals with benign nodules. In 7/32 patients (21.9%) there was a discrepancy between cytological findings and molecular results, which revealed a benign nodule and a PTC-like pattern, respectively. Upon a repeated examination of five of these patients about one year later, three were cytologically diagnosed with PTC (all patients had been operated on), and the diagnosis of the other two patients remained unchanged.Conclusions. The results have demonstrated that the molecular analysis of FNAB material is an informative means of the preoperative diagnosis of thyroid nodules as it allows identification of patients with suspected PTC before other diagnostically significant changes take place.Keywords: papillary thyroid carcinoma, fine-needle aspiration biopsy, preoperative diagnosis, molecular test